FACTORS AFFECTING STUDENTS’ WILLINGNESS TO SPEAK ENGLISH AT ELEVENTH GRADE OF SMA PERTIWI MEDAN - Chenny Adela Simamora; Siti Aisah Ginting (Universitas Negeri Medan, 2023)
This study is about Teachers’ Learning Media in Teaching Writing of Descriptive Text at SMP Negeri 37 Medan. The first aim of this research was to know what kinds of learning media are used by teachers in teaching writing of descriptive text and also to analyze the ways of using learning media in teaching writing of descriptive text. The second aim was to know the reasons using learning media in teaching writing of descriptive text by teachers. The data for this study was taken from the teachers who taught in the eight grade in SMP Negeri 37 Medan. The research design of this study was descriptive qualitative research. The data were collected in 3 ways by observing, recording, and interviewing. The data was analyzed based on Harmer (2002) theory. The teachers used kinds of learning media in teaching writing of descriptive text, they were: picture, the overhead projector, and whiteboard. In some cases, teachers also combined two kinds of learning media. The ways of using the learning media in teaching writing of descriptive text, they were: preparation, presentation, and follow-up. The reasons of using learning media by teachers, they were: availability of learning media by school, students’ condition, and students’ interest in used of learning media in the teaching learning process.